THE INFLUENCE OF WALKING EXERCISE TO DECREASE OF BLOOD SUGAR TO THE DIABETES MELLITUS SUFFERER TYPE 2 IN INTERNAL DISEASSE POLICLINIC PROF. DR. SOEKANDAR HOSPITAL MOJOKERTO - Hariyanto, Agus; Basuki, Duwi (Jurnal Keperawatan Bina Sehat, 2009)
Physical exercise is one of the Penthalogy therapy for diabetes mellitus sufferer especially diabetes mellitus type 2. Sport therapy execution precision is one of vital importance to get optimal benefit with prevents the happening of hipoglicemia complication when do physical activity. Therefore it is necessary to pay attention procedures in doing physical activity. Walking exercise is one of the easy choices and very effective light intensify. In fact there are many diabetes mellitus sufferer that don’t do physical exercise especially walking exercise.The aim of this Research is to analyze the influence of walking exercise to blood sugar degree depreciation in diabetes mellitus type 2 sufferers. Kind of this research that used is pre experiment and design Research that is one group sample pre test- post test with once measurement. Sample consists of 26 sufferer respondents diabetes mellitus type 2 that endure to take care of road at Internal Disease polyclinic in BRSD Prof. Dr. Soekandar Mojokerto 2008 that chosen by consecutive sampling.Data is gathered by observation and measurement with observation format instrument and blood sugar degree grader (glucometer) reagent dry ”easy-touch”.The result of this research shows that found walking exercise significant influence to blood sugar degree depreciation (r = 0,000) and (α = 0, 05). From this research result is known in pre test that is 12 respondents has blood sugar degree 201-250 mg/dl (34,3%) and in post test that is 15respondents has blood sugar degree between 151-200 mg/dl (42,9%). As known average blood sugar degree depreciation is 21-40 mg/dl pasa 14 respondents (40%). It is supposed as often as possible to do physical activities especially walking exercise, so blood sugar degree is getting controlled, so it won’t be happen a serious complication.